Pengaruh Konsumsi Minuman Kunyit Asam terhadap Penurunan Nyeri Dismenorea pada Remaja Di SMA Negeri 1 Kota Bengkulu Tahun 2024: Effect of Turmeric and Tamarind Drink Consumption on Reducing Dysmenorrhea Pain in Adolescents at SMA Negeri 1 Bengkulu, in 2024 - Aurilia, Nesi; Wahyuni, Elly; Sholihat, Suci; Septiyanti; Nugraheni, Diah Eka (JURNAL KEBIDANAN, 2024)
Dysmenorrhea is pain felt by women during menstruation. In Indonesia, the incidence of dysmenorrhea is estimated to reach 55% of women of productive age, the prevalence is 64.25% consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrher1. Data from the Ministry of Education and Culture for Bengkulu City showed that SMA Negeri 1 Bengkulu City had the third largest number of female students and the highest rate of dysmenorrhea with a percentage (96.6%). This study aims to determine the effect of consuming sour turmeric drinks on reducing dysmenorrhoea pain in adolescents at SMA Negeri 1 Bengkulu City. This type of research uses pre-experimental research methods by implementing a One Group Pretest Posttest Design. The population in this study were 280 female students in classes X and Data analysis in this study used univariate and bivariate analysis using the Pired T Test. The results of the study showed that the average before the intervention was given was 3.9111 and the average after being given the tamarind turmeric drink intervention was 0.7333, which means that there was a significant effect of consuming turmeric tamarind drinks on reducing dysmenorrhoea pain in adolescents with a P value of 0.000 (< 0.05) then there is an effect of consuming sour turmeric drinks on reducing dysmenorrhoea pain in adolescents at SMA Negeri 1 Bengkulu City in 2024.